Influence of Eccentricity on the Forming Grinding of Cycloidal Gear and Its Compensation - Minghui Zhang; Xiaozhong Deng; Jianxin Su (Jixie chuandong)
The influence of eccentricity on the gear grinding of the cycloidal gear is theoretically analyzed. By compensating the eccentricity， the gear grinding precision of the cycloidal gear is effectively improved. On the basis of the spatial geometric relationship between the grinder and the workpiece， the geometric model of the grinding error is established. According to the standard GB/T 10095.1—2008， the influence of the eccentricity on the pitch， helix and profile errors of the cycloid is analyzed. Based on the grinding principle of CNC cycloid gear forming gear grinding machine， a comprehensive compensation method of radial and tangential is proposed. The eccentric installation and grinding test of the cycloid wheel is verified by the domestic YK7350B CNC cycloid gear forming and grinding machine， which shows that the compensation method can effectively improve the forming and grinding accuracy of the cycloid wheel and reduce the cutting marks on the tooth surface.